Dynamic Wetting of Molten Polymers on Cellulosic Substrates: Model Prediction for Total and Partial Wetting - Pucci, Monica Francesca; Duchemin, Benoît; Gomina, Moussa; Bréard, Joël (Frontiers in Materials, 2020)
This work consists in an experimental investigation of forced dynamic wetting of molten polymers on cellulosic substrates and an estimation of models describing this dynamic. A previous work of Pucci et al. (Pucci et al. 2018) showed that for totally wetting liquids (as paraffin oils), temperature-induced variations in dynamic wetting are included into the capillary number (Ca) and then a master curve of dynamic contact angle (θd) as a function of Ca can be obtained. The hydrodynamic theory (HDT) correctly describes the dynamic wetting for Ca > 2 · 10−3. For lower Ca, a change in the dynamic wetting behavior was observed. Here, partially wetting liquids (polyethylene glycols, a.k.a. PEGs) at different molecular weight (Mn) were used at temperatures above their melting point to investigate the dynamic wetting behavior on cellulosic substrates for a large range of Ca. It was found that the dynamic curves of θd vs. Ca depend on Mn. Moreover, the HDT correctly describes the experimental measurements for Ca > 2 · 10−3. Below this threshold the dynamic contact angle decreases towards the static one. A linear correlation between parameters obtained fitting the HDT and the molecular weight of polymer was found. The prediction of dynamic wetting for low Ca (Ca < 2 · 10−3) with the molecular kinetic theory (MKT) was also evaluated and discussed.